Literature Review: Review of the Historical Evolution of Policies and Institutions of Community Based Management in Coastal Bangladesh - Dewan, Camelia (2012)
n this paper, we review the historical evolution of policies, projects and institutions 5 governing coastal polders in Bangladesh and the role of local communities in their management. This is done through three thematically divided sections. The first section is a historical analysis of the evolution of policies and projects on community participation in the water sector in Coastal Bangladesh. The second section is an organizational comparison of the two main implementing agencies, Bangladesh Water Development Board (BWDB) and Local Government Engineering Department (LGED). The third section look at BWDB and LGED’s experience of community based management and WMOs through the Small-Scale Water Resources Development Sector Project (SSWRDSP), and the Integrated Planning for Sustainable Water Management (IPSWAM). The Fourth section concludes with gaps in knowledge and avenues for future research.